Pengabdian Masyarakat melalui Terapi Pijat dan Relaksasi sebagai Intervensi Nonfarmakologis pada Fatigue Penderita Gagal Ginjal Kronis - Widayanti, Esti Dwi; Kuhu, Maisje M.; Sumedi, Taat (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Individuals with CKD who undergo hemodialysis frequently experience fatigue, a physical and psychological burden that diminishes daily functioning and quality of life. Fatigue is reported as one of the most common symptoms among dialysis patients, with a large proportion experiencing moderate to severe levels. Complementary therapies such as massage and relaxation techniques have been increasingly used to alleviate fatigue due to their accessibility, safety, and potential to support patient well-being. Objective: This community engagement program aimed to reduce fatigue among individuals with chronic kidney disease undergoing hemodialysis through guided hand and foot massage and progressive muscle relaxation involving family participation. Method: The intervention was conducted in Karangtengah Village, Kemangkon District, involving 20 participants diagnosed with CKD and receiving routine hemodialysis. Baseline data were collected through patient history and the FACIT-Fatigue Scale to measure fatigue severity. Family members were trained and accompanied to perform hand and foot massage as well as relaxation techniques. The program included group education sessions, practical demonstrations, and scheduled home visits over one month, with therapy performed twice weekly. Evaluation was carried out using the same fatigue instrument at the end of the intervention. Result: Before the intervention, 65% of participants demonstrated moderate fatigue (scores 18–34). After one month of consistent massage and relaxation therapy, 90% showed improvement with fatigue levels reduced to the mild category (scores 0–17). Participants also reported increased comfort, reduced muscle tension, and improved energy. Conclusion: Regular and guided massage combined with progressive relaxation effectively reduced fatigue among individuals undergoing hemodialysis. Family involvement strengthened adherence and continuity of therapy, highlighting its potential as a practical complementary approach to improving patient well-being.